EKSISTENSI ETIKA PROFESI KEGURUAN DALAM DUNIA PENDIDIKAN - Zulhimma, Zulhimma (IAIN PADANGSIDIMPUAN, 2013)
Teachers are guides towards students’ study success. They are for students’ future. Teachers mean models and guides for their students in any studies, characters and behaviours. Accordingly, teachers should have ethic for being educationists, teachers, instructors, guides and jury.